Odpowiedzi

2009-11-22T19:20:39+01:00
A) {4a-2=b
{3a+7b=1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
31a=1,5+14

b=4a-2
31a=15,5/31

b=4a-2
a=0,5

b=4*0,5-2
a=0,5

b=0
a=0,5

B) {5x=4-2y
{4x+y=3

5x=4-2y
y=3-4x

5x=4-2(3-4x)
y=3-4x

5x=4-6+6x
y=3-4x

5x-6x=-2
y=3-4x

-x=-2/*(-1)
y=3-4x

x=2
y=3-4*2

x=2
y=-2

C){6x-3y=9
{x+5y=-9.5

6x-3y=9
x=-9,5-5y

6(-9,5-5y)-3y=9
x=-9,5-5y

-57-30y-3y=9
x=-9,5-5y

-33y=9+57
x=-9,5-5y

-33y=66/:(-33)
x=-9,5-5y

y=-2
x=-9,5-5*(-2)

y=-2
x=-9,5+10

y=-2
x=0,5
2009-11-22T19:22:05+01:00
A)
{4a-2=b
{3a+7b=1,5

{b=4a-2
{3a+7(4a-2)=1,5

3a+28a-14=1,5
31a-14=1,5/+14
31a=15,5//31
a=0,5

{a=0,5
{b=4*0,5-2

{a=0,5
{b=0

b)
{5x=4-2y
{4x+y=3

{x=[(4-2y)/5]
{4x+y=3

4[(4-2y)/5]+y=3
[(16-8y)/5]+y=3
3,2-1,6y+y=3
3,2-0,6y=3/*10
32-6y=30/-32
-6y=-2//(-6)
y=(1/3)

{y=(1/3)
{x={[4-(2/6)]/5}

{y=(1/3)
{x=(11/15)


c)
{6x-3y=9
{x+5y=-9,5

{6x-3y=9
{x=-9,5-5y

69-9,5-5y)-3y=9
-57-30y-3y=9
-57-33y=9/+57
-33y=66//(-33)
y=-2

{y=-2
{x=-9,5-5*-2

{y=-2
{x=0,5